A revised name and new insights into the Middle Jurassic sauropod trackways from Portugal. A correction of Santos et al. 2009 - Vanda F. Santos; José J. Moratalla; Rafael Royo-Torres; Matteo Belvedere; Diego Castanera; Luis M.P. Ceríaco; Pedro Mocho; Marc Merino; Christian A. Meyer; Lara Sciscio (Acta Palaeontologica Polonica)
The Galinha dinosaur tracksite (Portugal) was declared a Natural Monument in 1996 and is currently designated as Ourém/Torres Novas Dinosaur Footprints Natural Monument. This tracksite yields a completely new and unique morphology of sauropod tracks from the Middle Jurassic (Bajocian–Bathonian). This new morphotype was named Polyonyx by Santos et al. (2009). However, recently it has been brought to our attention that this ichnotaxon name “Polyonyx” is preoccupied by the porcellanid decapod Polyonyx Stimpson, 1858 (Crustacea: Decapoda: Anomura: Porcellanidae). The priority is given to the latter and to avoid homonymy, the former is issued the new replacement name Galinhapodus igen. nov., creating the new replacement combination name Galinhapodus gomesi.